Evaluation of [F-18]F-DPA as a target for TSPO in head and neck cancer under normal conditions and after radiotherapy - Tuominen Sanni; Keller Thomas; Petruk Nataliia; López-Picón Francisco; Eichin Dominik; Löyttyniemi Eliisa; Verhassel Alejandra; Rajander Johan; Sandholm Jouko; Tuomela Johanna; Grönroos Tove J. (SPRINGER, 2022)
Background Many malignant tumours have increased TSPO expression, which has been related to a poor prognosis. TSPO-PET tracers have not comprehensively been evaluated in peripherally located tumours. This study aimed to evaluate whether N,N-diethyl-2-(2-(4-([F-18]fluoro)phenyl)-5,7-dimethylpyrazolo[1,5-a]pyrimidin-3-yl)acetamide ([F-18]F-DPA) can reflect radiotherapy (RT)-induced changes in TSPO activity in head and neck squamous cell carcinoma (HNSCC). Methods RT was used to induce inflammatory responses in HNSCC xenografts and cells. [F-18]F-DPA uptake was measured in vivo in non-irradiated and irradiated tumours, followed by ex vivo biodistribution, autoradiography, and radiometabolite analysis. In vitro studies were performed in parental and TSPO-silenced (TSPO siRNA) cells. TSPO protein and mRNA expression, as well as tumour-associated macrophages (TAMs), were also assessed. Results In vivo imaging and ex vivo measurement revealed significantly higher [F-18]F-DPA uptake in irradiated, compared to non-irradiated tumours. In vitro labelling studies with cells confirmed this finding, whereas no effect of RT on [F-18]F-DPA uptake was detected in TSPO siRNA cells. Radiometabolite analysis showed that the amount of unchanged [F-18]F-DPA in tumours was 95%, also after irradiation. PK11195 pre-treatment reduced the tumour-to-blood ratio of [F-18]F-DPA by 73% in xenografts and by 88% in cells. TSPO protein and mRNA levels increased after RT, but were highly variable. The proportion of M1/M2 TAMs decreased after RT, whereas the proportion of monocytes and migratory monocytes/macrophages increased. Conclusions [F-18]F-DPA can detect changes in TSPO expression levels after RT in HNSCC, which does not seem to reflect inflammation. Further studies are however needed to clarify the physiological mechanisms regulated by TSPO after RT.